KONSEP PENDIDIKAN ISLAM INTEGRATIF DALAM IDEOLOGI LIBERALISME - Akhmad Zaini (Universitas Islam Lamongan, 2021)
Liberalization of education is an educational ideology that is student-oriented, so that the long-term goal of education is to preserve and improve the existing social order by teaching each student how to deal with problems in his own life effectively. The concept of liberalism on education implicitly leads to the concept of integrative education